2020
DOI: 10.1109/access.2020.3012706
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hardware-Efficient Central Pattern Generator Model Based on Asynchronous Cellular Automaton Dynamics for Controlling Hexapod Robot

Abstract: This paper presents a novel hardware-efficient central pattern generator (CPG) model to realize a bio-inspired gait of a hexapod robot. The CPG model consists of a network of cellular automaton (CA) oscillators; thus, it can be implemented as a network of sequential logic circuits. Detailed analyses of nonlinear oscillation dynamics show that the oscillator that is driven by multiple asynchronous clocks is more suitable to realize the gait of the robot than an oscillator that is driven by a single clock or mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Subsequently, Stoop et al succeeded in demonstrating that the model enables the reproduction of a number of nonlinear hearing phenomena such as nonlinear compression, two-tone suppression, combination tone generation, and first (second) pitch shift [5]- [10]. Since then, there has been an increasing interest in implementing a cochlea model utilizing nonlinear oscillators on digital and analog electronic circuits [11]- [30]. Such an electronic circuit can be applied Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Stoop et al succeeded in demonstrating that the model enables the reproduction of a number of nonlinear hearing phenomena such as nonlinear compression, two-tone suppression, combination tone generation, and first (second) pitch shift [5]- [10]. Since then, there has been an increasing interest in implementing a cochlea model utilizing nonlinear oscillators on digital and analog electronic circuits [11]- [30]. Such an electronic circuit can be applied Fig.…”
Section: Introductionmentioning
confidence: 99%
“…(iv) The fourth method to model a nonlinear biological oscillator is by using asynchronous CA, which has a continuous state transition time and discrete states. Such a model is implemented by an asynchronous sequential logic [23]- [30]. Inspired by the Hopf-type cochlea [4]- [10], our group has proposed a cochlea model designed by the fourth method and has shown that the model can reproduce the frequencythreshold tuning curves of a mammalian cochlea [27].…”
Section: Introductionmentioning
confidence: 99%
“…Various gait patterns for locomotion can be achieved through assigning specific frequency and phase angles to individual oscillators in an array. Applications for locomotion control using Field Programmable Gate Arrays (FPGAs) with the aid of CPGs and coupled nonlinear oscillators have also been proposed [13][14][15]. Specifically, the HAFO has been used for robotic locomotion control by employing HAFOs as CPGs to tune walking patterns in a cooperative way [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This is an asynchronous cellular automaton (CA) model of a bio-inspired system with a continuous (state transition) time and discrete states (CTDS). A class CTDS bio-inspired model can be generally implemented in an asynchronous sequential logic circuit, e.g., [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been developing CPG models for hexapod robots belonging to the class CTDS system, which utilize fewer hardware resources for circuit implementation than models belonging to the class DTDS system [20][21][22][23]. Figure 1 shows conceptual diagrams of our CPG model studied in this paper.…”
Section: Introductionmentioning
confidence: 99%